From Governance to Poweranance: The Politics of Power in Public Administration - Isra Muksin (Pt. Anagata Sembagi Education, 2026)
This study examines public administration beyond the conventional lens of neutral governance by introducing the concept of poweranance, which emphasizes the role of power relations in shaping administrative practice. While governance frameworks highlight accountability, coordination, and institutional order, empirical evidence shows that administrative decisions are deeply influenced by political control, bargaining, and resource asymmetries among actors. A qualitative interpretive method was employed through document analysis of policy and regulatory texts and semi structured interviews with public administration practitioners across different governance contexts. The findings reveal that hierarchical accountability, performance management, collaborative networks, expert advice, and regulatory compliance are consistently mediated by power dynamics rather than purely procedural considerations. Administrative discretion, negotiation, and dominance emerge as key mechanisms through which governance principles are enacted. The discussion demonstrates that governance operates within political environments where actors strategically influence administrative outcomes. The study concludes that public administration is better understood as poweranance, where governance structures function within dynamic configurations of power. Recognizing this perspective provides a more realistic understanding of how policies and public services are produced in practice.